Research by Design (RbD) Method as a Process for Creating an Effective Museum Message - GRZONKA Aleksandra; SZEWCZENKO Anna (Architecture, Civil Engineering, Environment, 2025)
Contemporary exhibition design requires not only creating a message that engages the audience but also applying effective methods in the exhibition development process. This involves incorporating research findings into the design process as well as using tools available to the designer. This article discusses the methodology of design and implementation work and the results of research in design that form the basis for the implementation of exemplary exhibition projects at the Silesian Museum. The purpose of the paper is not only to present the specifics of this process, but also to identify the multifaceted and overarching role of the designer in the process of creating exhibition spaces. The presented examples of temporary exhibitions illustrate the diverse educational character and artistic dimension. The article also uses the main design categories to evaluate the analyzed exhibitions from the point of view of the necessary aspects in developing an engaging message for the viewer at the design and presentation levels. The outcome of the article is the identification of the main stages of the design process, along with the designer’s tools and activities, as well as guidelines for developing effective tools during the post-design research phase.